Evaluation of the growth-inducing efficacy of various Bacillus species on the salt-stressed tomato (Lycopersicon esculentum Mill.) - Patani, Anil; Prajapati, Dharmendra; Ali, Daoud; Kalasariya, Haresh; Yadav, Virendra Kumar; Tank, Jigna; Bagatharia, Snehal; Joshi, Madhvi; Patel, Ashish (Frontiers in Plant Science, 2023)
Plants are affected by salt stress in a variety of ways, including water deficiency, ion toxicity, nutrient imbalance, and oxidative stress, all of which can cause cellular damage or plant death. Halotolerant plant growth-promoting rhizobacteria (PGPR) could be a viable alternative for tomato plants growing in arid and semi-arid environments. The aim of this research was to isolate halotolerant plant growth promoting Bacillus sp. to promote tomato (Lycopersicon esculentum Mill.) growth and salt stress resistance.107 PGPR strains were isolated from the rhizospheres of ‘Kesudo’ (Butea monosperma Lam.), ‘Kawaria’ (Cassia tora L.), and ‘Arjun’ (Terminalia arjuna Roxb.) plants to test their plant growth promoting abilities, including indole-3-acetic acid, phosphate solubilization, siderophore production, and ACC deaminase activity. Five bacterial strains (Bacillus pumilus (NCT4), Bacillus firmus (NCT1), Bacillus licheniformis (LCT4), Bacillus cereus (LAT3), and Bacillus safensis (LBM4)) were chosen for 16S rRNA on the basis of PGPR traits. Tomato plants grown from PGPR treated seeds had significantly higher germination percentages, seedling growth, plant height, dry weight, and leaf area than PGPR untreated plants. Salt-stressed tomato plants inoculated with PGPR strains had higher total soluble sugar, proline, and chlorophyll content than non-inoculated plants, as well as higher SOD, CAT, APX, and GR activity. PGPR-inoculated salt-stressed tomato plants had lower MDA, sodium, and chloride levels than non-inoculated plants. In addition, magnesium, calcium, potassium, phosphorus, and iron levels were higher in PGPR treated plants when subjected to salt stress. These results indicate that halotolerant PGPR strains can increase tomato productivity and tolerance to salt stress by removing salt stress's negative effects on plant growth.